Faculty Senate, Minutes, September 25, 1997 - Faculty Senate, Valdosta State University (Valdosta, GA: Valdosta State University Archives and Special Collections)
Faculty Senate, Minutes, September 25, 1997. 7 pages.
1 electronic record. PDF/A. faculty-senate_19970925_minutes.pdf
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records